1995
DOI: 10.1111/j.1432-1033.1995.293_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Amyloid A4‐(1–40)‐Peptide of Alzheimer's Disease

Abstract: One of the principal peptide components of the amyloid plaque deposits of Alzheimer's disease in humans is the 40-amino-acid peptide 8-amyloid A4-( 1 -40)-peptide. The full-length A4-( I -40)-peptide was chemically synthesized and the solution structure determined by two-dimensional nuclear magnetic resonance spectroscopy and restrained molecular-dynamics calculations. Synthetic human A4-( 1 -40)-peptide was soluble and non-aggregating for several days in 40 % (by vol.) trifluoroethanol/water. All spin systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
340
3
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(382 citation statements)
references
References 39 publications
36
340
3
3
Order By: Relevance
“…Previous NMR studies demonstrated that the -(1-28) peptide folds into an ordered R-helical structure at pH 1-4 and 7-10 in aqueous solutions containing trifluoroethanol or micelles Talafous et al, 1994). More recent NMR studies of a -(10-35)-CONH 2 fragment suggest a turn-strand-turn motif between His13 and Val24 in aqueous solution (Lee et al, 1995), while the -(1-40) peptide forms two R-helical segments between Gln15-Asp23 and Ile31-Met35 in aqueous trifluoroethanol solution (Sticht et al, 1995).…”
Section: Biological Functions Of Nicotine and Its Relevance To Alzheimentioning
confidence: 99%
See 1 more Smart Citation
“…Previous NMR studies demonstrated that the -(1-28) peptide folds into an ordered R-helical structure at pH 1-4 and 7-10 in aqueous solutions containing trifluoroethanol or micelles Talafous et al, 1994). More recent NMR studies of a -(10-35)-CONH 2 fragment suggest a turn-strand-turn motif between His13 and Val24 in aqueous solution (Lee et al, 1995), while the -(1-40) peptide forms two R-helical segments between Gln15-Asp23 and Ile31-Met35 in aqueous trifluoroethanol solution (Sticht et al, 1995).…”
Section: Biological Functions Of Nicotine and Its Relevance To Alzheimentioning
confidence: 99%
“…An intriguing possibility is that nicotine may prevent the R-helix f -sheet conversion, which occurs during aggregation, by binding and stabilizing the small amounts of R-helical structure that may be present for monomeric -(1-42) peptide. The three-dimensional solution structure of the -(1-28) peptide in trifluoroethanol/ water and SDS-d 25 micelle solution is predominantly R-helical (Talafous et al, 1994) and is qualitatively similar to that for the -(1-40) peptide (Sticht et al, 1995). For the present study, we followed the binding of nicotine with the -(1-28) peptide in SDS-d 25 solution at pH 7.2.…”
Section: Shown Inmentioning
confidence: 99%
“…32 However, cluster A deviates from the ones found in NMR experiments of A␤ in TFE/water. 16 The average main chain RMSD between cluster A structure and the 20 NMR models of the 1AML.PDB is 9.89 Å, where structural superposition is done by using sequence alignment on 1-39 residues.…”
Section: -3mentioning
confidence: 99%
“…Slightly higher in energy are conformations with solely a turn around Val12-Leu17 residues and suchconformers that have a helical region in the N-terminal, i.e., similar to the one observed in NMR studies done in trifluoroethanol ͑TFE͒/water solution. 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation